Changes in dendritic complexity and spine morphology following BCG immunization in APP/PS1 mice - Qingqing Li; Xiao Wang; Zhao Hua Wang; Zhenzong Lin; Jieyi Yang; Jichun Chen; Rui Wang; Wenfeng Ye; Ya Li; Yingying Wu; Aiguo Xuan (Human Vaccines & Immunotherapeutics, 2022)
Bacillus Calmette – Guerin (BCG) is an immune regulator that can enhance hippocampal synaptic plasticity in rats; however, it is unclear whether it can improve synaptic function in a mouse model with Alzheimer’s disease (AD). We hypothesized that BCG plays a protective role in AD mice and investigated its effect on dendritic morphology. The results obtained show that BCG immunization significantly increases dendritic complexity, as indicated by the increased number of dendritic intersections and branch points, as well as the increase in the fractal dimension. Furthermore, the number of primary neurites and dendritic length also increased following BCG immunization, which increased the number of spines and promoted maturation. IFN-γ and IL-4 levels increased, while TNF-α levels decreased following BCG immunization; expression levels of p-JAK2, P-STAT3, SYN, and PSD-95 also increased. Therefore, this study demonstrates that BCG immunization in APP/PS1 mice mitigated hippocampal dendritic spine pathology, especially after the third round of immunization. This effect could possibly be attributed to; changes in dendritic arborization and spine morphology or increases in SYN and PSD-95 expression levels. It could also be related to mechanisms of BCG-induced increases in IFN-γ or IL-4/JAK2/STAT3 levels.